Baseline prostate atrophy is associated with lower tumor volume in men with prostate cancer on repeat biopsy. Issue 1 (April 2018) - Moreira, Daniel; Andriole, Gerald; Castro-Santamaria, Ramiro; Freedland, Stephen
Abstract Background Prostate atrophy (PA) is commonly identified in prostate biopsies. Previous studies suggest PA may be associated with lower PCa risk. However, it remains unclear whether PA is associated with smaller, less aggressive, and less advanced tumors. Thus, we sought to determine whether the presence and severity of baseline PA in men with initial biopsy negative for prostate cancer (PCa) is associated with PCa volume at 2- and 4-year repeat biopsy. Methods We performed a retrospective analysis of 927 men 50–75-years-old with negative baseline biopsy and positive 2- or 4-year repeat biopsy for PCa in the Reduction by Dutasteride of PCa Events study. PA (present or absent), PA severity (mild or moderate/marked), and tumor volume were determined by central pathology. The association of baseline PA with repeat biopsy PCa volume was evaluated with linear and Poisson regressions in uni- and multivariable analyses. Results PA was identified in 559 (60%) baseline biopsies and was mild in 491 (88%) and moderate/marked in 68 (12%). PA was associated with larger prostate volumes (P < 0.001). At 2-year biopsy, PA was associated with lower overall mean total tumor volume (2.21 vs. 2.94 µL;P = 0.016), mean number of biopsy cores involved (1.85 vs. 2.08;P = 0.016), mean percent of cores involved (18.4% vs. 20.7%;P = 0.008), average core involvement (0.23 vs. 0.29 µL;P = 0.019) and overall mean percent tumor involvement (1.82% vs. 2.33%;P = 0.018). Similar results were found in multivariable analysis and analysis of 4-year repeat biopsies. Compared to mild PA, moderate/marked PA was associated with greater reduction in tumor volume. Conclusion Amongst subjects with repeat prostate biopsy positive for PCa after negative baseline biopsy, the presence and severity of baseline PA were associated with lower PCa volume. This suggests PA may be associated with less aggressive PCa.